Representation and the Electoral College - Alexander, Robert M. 1972- (Oxford University Press, 2019)
"Nearly 800 proposals have been made to amend or abolish the Electoral College, and its divisiveness raises many questions. Does the body ensure representation across the country? Does the institution benefit some states at the expense of others? How does the process relate to an incoming president's legitimacy? Are presidential electors free to use their own judgement? Should the Electoral College exist at all? Much confusion surrounds this institution, in large part because of how the original Electoral College differs from its contemporary counterpart, the evolved Electoral College. This book helps readers to understand the distinction and how got where we are today. Focusing on the controversial 2016 election, in which Trump received nearly three million fewer popular votes than Clinton, Representation and the Electoral College shows how the Electoral College works to determine election outcomes. In exploring the origin, development, and practice of the Electoral College, this study also presents the most extensive analysis of presidential electors to date."--Back cover
Keywords: Electoral college / United States; Representative government and representation / United States; Repräsentative Demokratie; Wähler; Electoral college; Parlamentarismus; Repräsentation -- Politik; USA